RANCANG BANGUN PROTOTYPE PENGENDALIAN LENGAN ROBOT (ROBOTIC ARM) SEBAGAI PEMINDAH BARANG BERBASIS INTERNET OF THINGS - Syah Alam; Gunawan Tjahjadi; Nur Rahma Yenita; Supriyadi Supriyadi (LPPM, 2021)
This study proposes a prototype design of a robot arm control system based on the Internet of Things (IoT) by utilizing the NodeMCU microcontroller and the Blynk application. The NodeMCU microcontroller functions as a control system combined with four servo motors that are positioned as mechanical drives at the base, shoulder, elbow and grip of the robot arm. The angle settings of each motor are 180 °, 90 °, 60 ° and 90 ° which are used as actuators for lifting, gripping and moving loads. To control the robotic arm, the blynk application can be accessed via smartphone. From the results of the design and testing, it was found that the maximum load that could be moved was 20 grams with a transfer time of 46 seconds and a speed of 0.0054 seconds. The max-imum distance for moving goods is 25 cm and the types of goods being moved are those that have a rough sur-face. This research is useful as a solution for moving goods that can be controlled remotely